Influência dos ciclos de umedecimento e secagem na especiação do fósforo em rios intermitentes - Silva, Antonio Elves Barreto da (2022)
Intermittent rivers are ecosystems that spend most of the year dry. These environments have been studied mainly from the perspective of population and community ecology and environmental degradation. About the dynamics of elements, the studies are still incipient and the data obtained are not very concise. This study aimed to investigate the relationship between hydroperiods and availability, forms and amounts of phosphorus in intermittent rivers. Sediment and water collections were carried out in three hydrological periods based on theoretical models proposed for studies in intermittent ecosystems: Dry, Post dry, and Pre dry. Phosphorus was fractionated and data on texture, mineralogy, iron extraction, pH, eh, electrical conductivity, phosphorus in water, dissolved oxygen, and total organic carbon were obtained to support the discussion. The sciencemetric analysis tool was used to understand the evolution of the research topic over the years and its current status. Means comparison tests and discriminant function analysis were performed to measure differences and predominance of phosphorus fractions temporally and spatially. It is concluded that research related to intermittent rivers has increased continuously over the years, but research on nutrient cycling and dynamics is still few. The main fractions that control the phosphorus dynamics were P Oxyhydroxides (iron), P associated with phyllosilicates and hydroxides (Al) (F3a) and, P associated with refractory organic matter (F5). The proposed hypotheses were partially answered. Only the wetting and drying cycles are not able to change the element's dynamics, as this is strongly dependent on the soil matrix.